Can Governance at the Right Scale Increase Productivity? A Comparative Scoping Review - Krawchenko, Tamara (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2022)
Enhancing productivity is a common rationale for devolution, outsourcing and new institutional configurations and a recurring theme in public administration reforms. Functions such as urban planning, infrastructure development, water management, and transportation planning have clear spatial characteristics wherein their governance ideally spans their functional use and/or management. These considerations have led to municipal amalgamations and two-tier governance in an effort to consolidate functions and build economies of scale and to the creation of special purpose, intermediate or regional bodies to manage public investments and deliver specialised services. While there is a growing urban literature on governance at the right scale in certain policy areas, far fewer studies explore these factors in lower density places (towns and rural and remote areas). Moreover, how effective and efficient governance might boost productivity both within the institution and more generally, across the local/regional economy is underexplored. This paper takes stock of how governance at the right scale might improve public sector productivity in different types of places—urban, rural and remote. It draws on theoretical, empirical and policy literature to explore how scale matters to public sector productivity and governance.